ANALISIS CARA-CARA GURU MEMOTIVASI BELAJAR SISWA PADA PEMBELAJARAN IPS SEKOLAH DASAR GUGUS 7 KECAMATAN TAMPAN KOTA PEKANBARU - Weni Zulkaidah; Hendri Marhadi; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is motivated by the lack of students’ motivation to learn. In learning, students tend to play around, indifferent, sleepy, and ask permission at the time of the learning process is ongoing. Therefore, it needs motivation from teachers who teach. This research aims to determine what the most dominant way used by teachers in motivating students' learning on Social Science learningin SD gugus 7 Tampan district, Pekanbaru City. This research uses descriptive quantitative with the subject consisted of 60 teachers. Data collection technique used is questionnaire technique. based on the results of overall research, the most dominant is to provide an opportunity (competition) with a percentage of 91.2% categorized as always and give the results of learning to students with percentage of 90.3% categorized as always. A small percentage that teachers use in motivating is in giving rewards with a percentage of 67.1 categorized as often. This showed the teachers of Gugus 7 Tampan district Pekanbaru City in teaching motivated students by giving the opportunity for students to compete in the competition and announcing the learning result to the students.Keywords: Analysis, How Teachers Motivate Student Learning, Social Science Learning